2013
DOI: 10.1039/c3nr34276j
|View full text |Cite
|
Sign up to set email alerts
|

Nano–bio effects: interaction of nanomaterials with cells

Abstract: With the advancements in nanotechnology, studies on the synthesis, modification, application, and toxicology evaluation of nanomaterials are gaining increased attention. In particular, the applications of nanomaterials in biological systems are attracting considerable interest because of their unique, tunable, and versatile physicochemical properties. Artificially engineered nanomaterials can be well controlled for appropriate usage, and the tuned physicochemical properties directly influence the interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
162
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(163 citation statements)
references
References 212 publications
0
162
0
1
Order By: Relevance
“…On the other hand, the cytotoxicity of NPs may also be used to enhance the antibacterial efficacy in light-activated antimicrobial surfaces [29]. Although there is a vast literature on nanoparticle-cell interactions [30][31][32], a detailed physicochemical description of adverse outcomes relevant to in vivo behaviour does not exist. In fact, most of the published studies offer no conclusive nano-toxicological data for in vitro models which might make it possible to predict an in vivo response.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the cytotoxicity of NPs may also be used to enhance the antibacterial efficacy in light-activated antimicrobial surfaces [29]. Although there is a vast literature on nanoparticle-cell interactions [30][31][32], a detailed physicochemical description of adverse outcomes relevant to in vivo behaviour does not exist. In fact, most of the published studies offer no conclusive nano-toxicological data for in vitro models which might make it possible to predict an in vivo response.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the surface properties of QDs determine their bio-interface interactions, cellular endocytosis and intracellular distribution, in vivo biodistributions, metabolism, and fate. [60][61][62][63] Engineering surface of QDs therefore becomes highly important as this process can improve these properties and 35 introduce additional functions. 10 Medintz et al recently summarized the strategies for surface modification and bioconjugation of QDs.…”
Section: Surface Modification Of Qdsmentioning
confidence: 99%
“…6 It has been shown that non-specific interactions with the NPs can alter SLB structure and elasticity. 5 NPs can adhere to the lipid bilayer and cause changes in the lipid phase, 7 induce formation of lipid domains [8][9] or pores and extract lipids 10 inducing lipid bilayer disruption. [11][12] Physical chemical properties of NPs, 5,13 such as size, 4,11,[14][15] charge 12,16 and surface chemistry [17][18][19][20] are the main factors modulating NP-membrane interactions.…”
Section: Introductionmentioning
confidence: 99%
“…3 In fact, model membranes are versatile systems whose composition and structure can be precisely controlled and customized capturing essential aspects of the real membranes, without the influence of cell metabolism and growth. 5 Moreover, model membranes allow the use of a wide range of powerful techniques, like quartz crystal microbalance and scattering techniques, that would be hardly applicable to real membranes. 2 Supported lipid bilayers (SLBs) represent one of the most used and versatile models for biological membranes.…”
Section: Introductionmentioning
confidence: 99%